Proyecto de factibilidad para la creación de una empresa productora de vinagre blanco y su comercialización en el cantón Yantzaza provincia de Zamora Chinchipe - Gutiérrez Apolo, Moraima Elizabeth (2016)
This research was conducted in the Yantzaza province of Zamora Chinchipe, canton in order to implement a feasibility project for the creation of a company producing and marketing white vinegar in the canton Yantzaza province of Zamora Chinchipe. A market study was conducted in the canton Yantzaza with a sample of 372 people and 80 local, with the analysis of the surveys it shows that there is an effective demand of 122,588 bottles of white vinegar 250 ml, and there is an offer on the market 36,380 bottles of 250 ml white vinegar and unmet demand for 86,208 bottles of white vinegar 250 ml, which determines that the project is viable. The product bearing the name "La Sabrosa" white vinegar, the same that is in the presentation of 250 ml. Its price is set based on production costs plus a profit margin, distribution will take place in major markets, shopping centers, warehouses, shops and health food centers. The installed capacity of the plant is 96,000 bottles of white vinegar per year, as a new project initially the company will begin its operations with 78% of its installed capacity in the last year used 96% of capacity leaving 4% for the unexpected to occur in the course of its operations. Through advertising and product positioning of the company in the market of Canton Yantzaza be achieved, advertising will be through radio and local newspapers. In the technical study the macro and micro location, size and project engineering, process diagrams, technical requirements as well as furniture and fixtures was established. The company will be located in the neighborhood Pita Av. Yaguarzongo and Calle Amazonas corner. an administrative study in which it was established the company as a limited liability company, which will be registered with the Superintendency of Companies under the nomination of "INDUSTRIAL COMPANY YANTZACENSE" was performed, a manual function allowing you designed your staff know each of their roles in the stands. The financial study in which investments and financing are detailed by the addition of partners and external funding needed to launch the project is presented. The required investments are in fixed assets, deferred assets and current assets or working capital, fixed assets amounted to the sum of $ 15,136.40, deferred tax assets of $ 1459.50 and a working capital is the amount of 6556.43 dollars giving an overall investment of $ 23,152.33 Investments are two kinds of internal member contributions amounting to $ 11,152.33 48.17% equivalents and foreign investment through the National Development Bank of $ 12,000.00 equivalent to 51.83%. The operating budget for the first year is $ 80,468.85, sales revenue amounted to 90,125.11, with a profit margin of 12%. In the economic evaluation we have a net present value is $ 30,348.28, the internal rate of return is 36.04%, which is higher than the rate of market opportunity, Benefit Cost Ratio is 1.12, is say for every dollar invested the company has a profit of 0.12 cents, the investment is recovered in 2 years, 6 months, 18 days, the project is not sensitive to an increase in the maximum costs by 4,18 and reduced the minimum income of 3.73, higher than the percentages the project becomes sensitive.